(untitled) (KYAMC Journal, 2017)
Struma ovarii (literally: goitre of the ovary) is a rare form of monodermal teratoma that contains mostly thyroid tissue. The vast majority are benign tumours; however, malignant tumours of this type is found in a small percentage of cases. It is most common between the ages of 40 and 60 years and accounts for approximately 5 percent of all ovarian teratomas. Here we present a case of left sided struma ovarii. This patient is a 39 years’ woman from Bhobanipur, Rajbari, Bangladesh. She noticed bleeding per vagina, abdominal swelling and left pelvic region mass for few months. Clinical & imaging examination revealed ascites and left ovarian neoplastic lesion. After excision biopsy, histopathological examination was performed. Microscopically, it shows ovarian tissue but predominantly composed of mature thyroid tissue which are diagnostic key feature of struma ovarii. KYAMC Journal Vol. 7, No.-1, Jul 2016, Page 734-735